The Relationship between Waste Management Practices and Human Health: New Perspective and Consequences - Oluwagbayide, Samuel Dare; Abulude, Francis Olawale; Akinnusotu, Akinyinka; Arifalo, Kikelomo Mabinuola (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
Waste management, an integral aspect of modern life, exerts a profound influence on both public health and the environment. While existing research explores the environmental impact of various waste management practices, there is a paucity of studies investigating the direct health effects on humans from these practices. This article aims to address this gap by examining the intricate interplay between specific waste management strategies, such as open burning or landfill leachate management, and their potential to cause respiratory illnesses, birth defects, or other health problems in urban areas. Drawing from existing knowledge and recent research, it underscores the imperative of adopting an integrated waste management approach that harmonizes environmental preservation and health considerations. Furthermore, the review spotlights emerging technologies and innovative methodologies that hold promise in mitigating potential health hazards associated with conventional waste management practices. It accentuates the intricate connection between waste management and human health, underscoring the need for holistic strategies that encompass both community welfare and environmental sustainability. This paper advocates for sustainable waste management approaches that not only alleviate health concerns but also promote resource recovery and community engagement. Policymakers, urban planners, and stakeholders are encouraged to collaborate in the adoption of effective waste management methods that safeguard both the environment and human health. By recognizing the intrinsic link between environmental and health issues, a harmonized approach can be forged to address them.